Microcin J25 Uptake: His5 of the MccJ25 Lariat Ring Is Involved in Interaction with the Inner Membrane MccJ25 Transporter Protein SbmA - de Cristobal, Ricardo Ezequiel (2006)
Escherichia coli microcin J25 (MccJ25) is a plasmid-encoded antibiotic peptide consisting of 21 L-amino acid residues (G1 -G-A-G-H5 -V-P-E-Y-F10-V-G-I-G-T15-P-I-S-F-Y20-G). E. coli RNA polymerase (RNAP) is the intracellular target of MccJ25. MccJ25 enters cells after binding to specific membrane transporters: FhuA in the outer membrane and SbmA in the inner membrane. Here, we studied MccJ25 mutants carrying a substitution of His5 by Lys, Arg, or Ala. The inhibitory effects on cellular growth and in vitro RNAP activity were determined for each mutant microcin. The results show that all mutants inhibited RNAP in vitro. However, the mutants were defective in their ability to inhibit cellular growth. Experiments in which the FhuA protein was bypassed showed that substitutions of MccJ25 His5 affected the SbmA-dependent transport. Our results thus suggest that MccJ25 His5 located in the lariat ring is involved, directly or indirectly, in specific interaction with SbmA and is not required for MccJ25 inhibition of RNAP.